Variability in the physical and chemical properties of type I Portland cement - Reyes, Evelyn E. (Animo Repository, 2003)
Cement is a highly standardized product and as long as the selection of cement is correct with respect to the desired objectives of concrete, the concrete most likely gives very good service performance. However, being sourced from different manufacturers, quality variability in Type I Portland Cement should be considered. In this regard, the author aims to review the company’s standard operating procedures, to evaluate the variability in the physical and chemical properties of Type I Portland Cement and to provide pertinent information on the effects of this variability based on a thorough review of related literature. To achieve this objective accurately, the operation of the batching plant including procurement, the manner of acceptance of the raw materials, the batching itself and its quality control were examined. Samples of different brands of cement were randomly taken and subjected to physical and chemical tests as per ASTMC150 standards. A total of eleven samples were prepared, four of which came from two batches by one manufacturer and two of which came from a single batch of one producer. Further tests on other chemical properties not stated in the current standards such as: alkalis, oxides, complexes and ratios were also carried out. A thorough literature review was conducted to determine possible effects of the variations being distinguished to the properties and performance of cement itself and of concrete as well. Based on the test results obtained, all the samples have complied to the ASTMC150 standards except for Brand F which failed in Loss on Ignition test. Further analysis showed that there was a remarkable variation in MgO content, Insoluble Residue, Loss on Ignition, SO3 content, Na2O content, freelime, fineness, C3S andC2S content and C3A/SO3. Each of this property has its own effect on its performance. Studies show that the common consequences of variations in cement composition brought about by different proportioning of the chemical components are extremely delayed setting, fast setting, rapid stiffening, thermal cracking and poor workability. Since, the properties of cement can really vary in a disturbing manner from manufacturer to manufacturer and even from batch to batch from any single producer, it is for the benefit of the company and its clients to establish a close coordination with the manufacturer so as to be aware of the current modification, shall there be any, in the cement production. It is best that the mill certificate/test certificate that comes with the cement can and should be used to do more than just show that the cement meets relevant specifications. Likely, by tracking the changes in cement chemistry the company will be able to predict their influence on the performance of their product.